MECHANISTIC INSIGHT INTO MEDICINAL PROPERTIES OF INDONESIAN DIVERSE MANGROVE SPECIES: A REVIEW - MUHTADI, MUHTADI; PAMBUDI, DWI B.; MARYATI, MARYATI (International Journal of Applied Pharmaceutics, 2024)
Mangrove ecosystems in Indonesia harbor a rich diversity of plant species, some of which have been traditionally recognized for their medicinal properties. This study aims to provide mechanistic insights into the medicinal potential of various mangrove species found in Indonesian coastal regions. Through a comprehensive analysis of pharmacological activities and underlying mechanisms, our research seeks to elucidate the therapeutic properties of these diverse mangrove plants. The key terms "Mangrove", "Pharmacological", and "Indonesia" used for searching in three online databases: Science Direct, PubMed, and Google Scholar. The investigation into the pharmacological properties of mangrove species revealed versatile mechanisms of action. Notably, a convergence is observed in their antioxidant mechanisms, as exemplified by Aegiceras corniculatum, Avicennia marina, and Rhizophora mucronata, showcasing robust effects in DPPH, ABTS, and FRAP assays. Additionally, the study highlights significant findings in the realm of anti-inflammatory activities. Mangrove species like Aegialitis rotundifolia, Ceriops decandra, and Rhizophora apiculata demonstrate notable anti-inflammatory effects by inhibiting enzymes like LOX and responding positively to carrageenan induction. A commonality is unveiled in antibacterial effects, with species like Avicennia marina, Ceriops tagal, and Excoecaria agallocha exhibiting potent antibacterial properties in agar diffusion assays. These findings underscore the potential of mangrove species in combating microbial infections through distinct antibacterial mechanisms. Furthermore, understanding the mechanisms behind the medicinal properties of Indonesian mangrove species is crucial for both conservation efforts and the development of novel pharmaceuticals.